THE CONSUMER PROTECTION ISSUES TOWARD THE TRADEMARK CIRCULATION OF THE COUNTERFEIT HEALTH PRODUCTS - Ryan Adhyatma Cakrawibawa; Kholis Roisah (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2019)
This research purpose is to analyze the consumer legal protection efforts and reviewing obstacle factor of implementation of consumer protection related to the trademark circulation of the counterfeit health products in Central Java. This research carried out is a empirical research.. The collecting data used are library research and field studies. The results of this study indicate that There so many parties that involved to handle this case in regard with The Consumer legal protection related to the trademark circulation of health product including, Drug and Food Inspection Agency, Health Office, Industry and Trade Office, and Central Java Special Criminal Review of the Central Java Regional Police. The counterfeiting trademark and health products will be handled by the Commercial Court and Drug and Food Inspection Agency. The criminal legal protection by giving penalties to people who have committed crimes and trademark violations. The factors inhibiting the implementation of the consumer legal protection related to the trademark circulation of health product in Central Java: the lack of the public awareness toward the counterfeit trademark of health product and the lack of the public awareness to report the existence of counterfeit drugs to the authorities.